The anesthetist’s choice of inhalational vs. intravenous anesthetics has no impact on survival of glioblastoma patients - Schmoch, Thomas; Jungk, Christine; Bruckner, Thomas; Haag, Sabine; Zweckberger, Klaus; Deimling, Andreas von; Brenner, Thorsten; Unterberg, Andreas; Weigand, Markus A.; Uhle, Florian; Herold-Mende, Christel (Neurosurgical review, 2021)
Recent data suggest that the type of anesthesia used during the resection of solid tumors impacts the long-term survival of patients favoring total-intravenous-anesthesia (TIVA) over inhalative-anesthesia (INHA). Here we sought to query this impact on survival in patients undergoing resection of glioblastoma (GBM). All patients receiving elective resection of a newly diagnosed, isocitrate-dehydrogenase-1-(IDH1)-wildtype GBM under general anesthesia between January 2010 and June 2017 in the Department of Neurosurgery, Heidelberg University Hospital, were included. Patients were grouped according to the applied anesthetic technique. To adjust for potential prognostic confounders, patients were matched in a 1:2 ratio (TIVA vs. INHA), taking into account the known prognostic factors: age, extent of resection, O-6-methylguanine-DNA-methyltransferase-(MGMT)-promoter-methylation-status, pre-operative Karnofsky-performance-index and adjuvant radio- and chemotherapy. The primary endpoint was progression-free-survival (PFS) and the secondary endpoint was overall-survival (OS). In the study period, 576 patients underwent resection of a newly diagnosed, IDH-wildtype GBM. Patients with incomplete follow-up-data, on palliative treatment, having emergency or awake surgery; 54 patients remained in the TIVA-group and 417 in the INHA-group. After matching, 52 patients remained in the TIVA-group and 92 in the INHA-group. Median PFS was 6 months in both groups. The median OS was 13.5 months in the TIVA-group and 13.0 months in the INHA-group. No significant survival differences associated with the type of anesthesia were found either before or after adjustment for known prognostic factors. This retrospective study supports the notion that the current anesthetic approaches employed during the resection of IDH-wildtype GBM do not impact patient survival.